LEGAL STATUS, CLASSIFICATION, AND FEATURES OF ELECTRONIC CONTRACTS - Anatolyevna Kirillova, Elena; Sergey , Sergey; Aleksandrovna Kovaleva, Olga; Pavlovna Baskakova, Natalia; Tamindarovich Fatkulin, Safargaley (Revista Inclusiones, 2020)
The research is devoted to the study of the legal status and features of electronic contracts, which have become widespread due to the common usage of telecommunications means. The main purpose of the study is to classify and consider the legal characteristics of electronic transactions, as well as determine the effective scope of their application. When writing the article, the methods of collecting and studying isolated facts, generalization, scientific abstraction, cognition of laws, as well as the methods of objectivity, concreteness, pluralism were used. The study offers an original definition of electronic transaction, which should be understood as actions of participants in civil law turnover aimed at the emergence, change, and termination of civil relations, based on the exchange of electronic data and created using electronic means and analogues of a handwritten signature.